(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
Social networking technology has given rise to a unique form of anxiety in the adolescent population: the fear of missing out (FoMO). Research has demonstrated that FoMO may negatively impact adolescent health. This article describes how existential therapy may be effective in the prevention and treatment of social media-induced anxiety.